DIGITALISASI UMKM DESA TIMBANG LAWAN MELALUI PEMETAAN USAHA DI GOOGLE MAPS SEBAGAI STRATEGI PENINGKATAN VISIBILITAS DAN AKSESIBILITAS KONSUMEN - Meisarah, Helfina; Mulyana, Sri; Wulandari, Wulandari; Anazra, Davania; Samsudin, Samsudin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to increase the visibility and accessibility ofTimbang Lawan Village UMKM through the use of Google Maps as a means of digitizing business locations. The activities were carried out through a qualitative descriptive approach in the form of direct assistance to UMKM actors through the Student Creativity Program(PKM) and Real Work Lectures (KKN). The stages of the activity includedsocialization of the importance of digitization, collection of business profile data, business registrationon Google Maps, and training in digital profile management. The resultsof the activities show that businesses that have been registered on Google Maps have experiencedincreased visibility and consumer trust because location information, photos,and customer reviews can be easily accessed. Location-based digitizationhas proven to be an effective strategy in increasing exposure and consumer accessto local products. However, there are still challengessuch as low digital literacy and limited internet networks.